Análise da relação dos modelos organizacionais e excelência operacional em uma indústria moveleira - Slaviero, Gilmar Junior (My University, 2025)
This study explores the relationship between operational excellence and organizational models in the furniture industry. Operational excellence is defined as the pursuit of processo optimization, waste reduction, and qulity enhancement, while organizational models are structures that determine how and organization is managed and operates. The primary objective of this research is to analyze the relationship between organizational models and operational excellence within the context of the furniture company Florense. To achieve this objective, the theorical framework covers: concepts and principles of operational excellence, measurements of operational excellence, types and characteristics of organizational models, and the interrelationship between these models and operational excellence. The methodology involved a survey conducted in two main stages: gathering and understanding respondents, followed by data analysis. Exploratory factor analysis was used to identify latent factors in the data, based on a questionnaire administered to the company’s employees. The key findings revealed seven critical factors influencing operational excellence, including results orientation, flexibility, value addition in process, autonomy and quality monitoring, employee involvement, improvement methods, and respect. The analysis indicated that Florense is at an advanced maturity stage in operational excellence but identified areas for improvement. Significant insights include the maturity level os operational excellence and the identification of key factors, along with recommendations for continuous improvement. Limitations include the need to validate results in other contexts and sectors. Future studies should investigate the application of organizational models in other industries and define performance indicators to monitor the evolution of operactional excellence over time.[resumo fornecido pelo autor]
O tema deste trabalho é a relação entre excelência operacional e modelos organizacionais em uma indústria moveleira. A excelência operacional é entendida como a busca por otimização de processos, redução de desperdícios e aprimoramento da qualidade, enquanto os modelos organizacionais são estruturas que definem como uma organização é gerida e operada. O objetivo geral deste estudo é analisar a relação entre os modelos organizacionais e a excelência operacional no contexto de uma indústria do ramo moveleiro, com foco na empresa Florense. Para atender a esse objetivo, os assuntos organizados no referencial teórico incluem: conceitos e princípios de excelência operacional, medições de excelência operacional, tipos e características de modelos organizacionais, e a inter-relação entre os modelos e a excelência operacional. O método desenvolvido foi uma pesquisa survey, conduzida em duas etapas principais: levantamento e compreensão dos respondentes, seguido pela análise dos dados coletados. Utilizou-se a análise fatorial exploratória para identificar fatores latentes nos dados, e a pesquisa baseou-se em um questionário aplicado aos colaboradores da empresa. Os principais resultados revelaram a existência de sete fatores chave que influenciam a excelência operacional, incluindo orientação para resultados, flexibilidade, agregação de valor nos processos, autonomia e monitoramento da qualidade, envolvimento dos colaboradores, métodos de melhoria e respeito. A análise mostrou que a Florense está em um estágio avançado de maturidade em excelência operacional, mas com áreas para melhoria. Destaca-se pontos relevantes desta pesquisa ter gerado insights sobre a maturidade da excelência operacional e a identificação de fatores chave, além de propor recomendações para melhoria contínua. Para estudos futuros, recomenda-se investigar a aplicação dos modelos organizacionais em outras indústrias e definição de indicadores de desempenho para verificar a evolução da excelência operacional ao longo do tempo. [resumo fornecido pelo autor]
Keywords: Desenvolvimento organizacional; Indústria de móveis; Cultura organizacional; Organizational change; Furniture industry and trade; Corporate culture